Islamic Law and Gender: The Collapse of the Oligarchical-Patriarchal Culture in the Konawe Region of Southeast Sulawesi - Ipandang Ipandang (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2020)
This article focuses on the efforts of women in the Konawe Region of Southeast Sulawesi who seek to gain an egalitarian position in the midst of oligarchical-patriarchal culture. Divorce claims as a trend of regional social become the main discourse on the dynamics of marriage law – in this context of Islamic law perspective. It is ordinarily for this research to use a qualitative approach aimed at forming substantive theories based on the concept of empirical data. The informants of this article were determined using a purposive technique, data collection techniques using in-depth interviews and participant observation, and the interactive model of Miles and Hubermann was used as a data analysis model. This research conclusively found that the power of oligarchic-patriarchal culture lies and legitimized by the interpretation of Islamic religious texts from the Qur’an and Sunnah. This effort also appears massive in the form of